Impact of Public Education Expenditure on Income Inequality in Pakistan - Nawaz, Muhammad; Shah, Tilawat (The Lighthouse Journal of Social Sciences, 2022)
The aim of the study was to investigate how public expenditure on education affects income inequality in Pakistan by analyzing time series data covering the years 1975 to 2018. To accomplish this, the auto regressive distributed lag model (ARDL) was used, as the data was stationary at different levels. The F-Bound co-integration test indicated the presence of a long-term relationship amid government expenditure on tutoring and income inequality. The results of long-term ARDL model revealed that public expenditure on education, GDP growth, and tertiary student enrollment have a damaging and substantial impact on income disparity. In addition, the ECM value suggested that there is a 7.3% rate of adjustment between the dependent and independent variables in successive years. These findings indicate that increasing funds allocated to education and reducing unemployment rates are crucial policy options for the government to reduce income inequality and improve income distribution in Pakistan.